Factors Influencing Drug Uptake during Mass Drug Administration for Control of Lymphatic Filariasis in Rural and Urban Tanzania - Kisoka, William J.; Simonsen, Paul E.; Malecela, Mwelecele N.; Tersbøl, Britt P.; Mushi, Declare L.; Meyrowitsch, Dan W. (PLOS ONE, 2014)
Background In most countries of Sub-Saharan Africa, control of lymphatic filariasis (LF) is based on annual mass drug administration (MDA) with a combination of ivermectin and albendazole. Treatment coverages are however often suboptimal for programmes to reach the goal of transmission interruption within reasonable time. The present study aimed to identify predictors and barriers to individual drug uptake during MDA implementation by the National LF Elimination Programme in Tanzania. Methods A questionnaire based cross sectional household survey was carried out in two rural and two urban districts in Lindi and Morogoro regions shortly after the 2011 MDA. 3279 adults (≥15 years) were interviewed about personal characteristics, socio-economic status, MDA drug uptake among themselves and their children, reasons for taking/not taking drugs, and participation in previous MDA activities for LF control. Findings The overall drug uptake rate was 55.1% (range of 44.5–75.6% between districts). There was no overall major difference between children (54.8%) and adults (55.2%) or between females (54.9%) and males (55.8%), but the role of these and other predictors varied to some extent between study sites. Major overall predictors of drug uptake among the interviewed adults were increasing age and history of previous drug uptake. Being absent from home during drug distribution was the main reason for not taking the drugs (50.2%) followed by clinical contraindications to treatment (10.8%), missing household visits of drug distributors (10.6%), and households not being informed about the distribution (9.0%). Conclusion Drug uptake relied more on easily modifiable provider-related factors than on individual perceptions and practices in the target population. Limited investments in appropriate timing, dissemination of accurate timing information to recipients and motivation of drug distributors to visit all households (repeatedly when residents are absent) are likely to have considerable potential for increasing drug uptake, in support of successful LF transmission elimination.